58 THE EFFECTS OF QUINIDINE AND ITS CHIRAL ISOLATES ON ERG-1SM POTASSIUM CURRENTS AND CORRELATION WITH GASTROINTESTINAL AUGMENTATION. (1st March 2006) - Cvetanovic, I.; Lin, C.; Ranade, V.; Somberg, J. C.
Abstract : Erg-1sm potassium channel has been recently reported to participate in modulation of gastrointestinal contractility. Since quinidine inhibits cardiac potassium channel and augments gastrointestinal contractility, it was thought that quinidine (Q) may affect erg-1sm. Studies were undertaken to evaluate the effects of Q and its chiral isolates on gastrointestinal erg-1sm potassium current and correlate these effects with colon contractility. Chiral separation (HPLC technique), mass spectrometry, and optical rotation determination were performed. The erg-1sm potassium channel was expressed in Xenopus oocytes and the two-electrode patch clamp technique was employed for recording. An isolated rat colon preparation was employed to measure changes in contractility. As a result of chiral separation, two peaks were obtained with elution times of 8.31 and 8.66 minutes all with a MW of 324; the optical rotations of racemate, isolates X and Y were + 258°, ± 0°; + 217°, respectively. The percentage changes in amplitudes of colon contraction (from baseline) were determined at different concentrations of Q and the two isolates in five experiments in each group. Quinidine 0.1, 1, and 10 μM increased contractility by 79 ± 34, 125 ± 42, 217 ± 51 ( p ≥ .05) for isolate X and 70 ± 20, 115 ± 32, 272 ± 32 ( p ≥ .05), and 22 ± 12, 46 ± 17, 59 ± 22 for isolate Y. The inhibition of erg-1sm currents by Q was 19 ± 4, 21 ± 5, and 48 ± 6 ( p ≥ .05), respectively, for isolate X, 20 ± 4, 23 ± 5, 39 ± 7 ( p ≥ .05), and for isolate Y, 22 ± 4, 21 [x 4, 31 ± 6. One chiral isolate and Q markedly augment contractility, while Q and the two chiral isolates inhibit the erg-1sm potassium currents to a similar extent. These results suggest that erg-1sm inhibition does not explain GI contractile augmentation caused by the Q racemate and its chiral isolates.